Arabic Language Learning Strategy: A Study of Learning in Madrasah Based on Boarding Boards - Rahmaini Rahmaini (AL-ISHLAH: Jurnal Pendidikan, 2023)
Arabic has become one of the "mandatory" everyday languages in Islamic boarding schools (as well as English). Of course, students (santri) who study at madrasas based on Islamic boarding schools receive additional teaching materials related to strengthening Arabic language skills. This study seeks to describe Arabic learning strategies in Islamic boarding schools based on Islamic boarding schools. The background of this research is at MTsS Raudhatusshalihin Kutacane, Southeast Aceh. This study uses a qualitative approach with a descriptive study method. Researchers carry out research actions in the field (field research) in an effort to obtain data through observation, interviews, and document studies. The results of this study found that the Arabic language learning strategy as a form of strengthening students' Arabic skills was characterized by 3 (three) aspects, namely the strategy of strengthening vocabulary memorization and singing popular songs (translated from Indonesian to Arabic), as well as a combination of learning in madrasas and internal boarding schools. This is based on the madrasa's efforts to effectively issue internal madrasa policies by characterizing Islamic educational institutions under the auspices of Islamic boarding schools. Through this research, it is hoped that it can become a new scientific treasure in improving students' Arabic skills in madrasas.